Achieving exceptional wear resistance in cemented carbides using B2 intermetallic binders. (15th January 2023) - Lou, Ming; Chang, Keke; Xu, Kai; Chen, Leilei; Lv, Jian; Du, Yujie; Chen, Xiang; Wang, Liping
Abstract: Conventional strategy for designing wear-resistant composites relies on the immersion of a carbide skeleton into ductile binders to impart necessary strength and deformability but sometimes overlooks the deformation compatibility, rendering the composites vulnerable to premature wear failures. In this work, extensive binder extrusion was specifically noted on traditional cemented carbides during sliding in absence of oxides protection. To alleviate this situation, we designed the WC-CoFeAl composites with a novel B2_CoFe binder phase structure, as per the calculated phase diagrams, in comparison to the WC-CoAl and WC-Co composites that respectively incorporate a single α-Co phase and a mixture of α-Co and ε-Co phases. The WC-CoFeAl reveals an exceptional binder extrusion resistance and realizes a ≥50% wear reduction within a temperature range of 25–400 °C. Originating from the intrinsically high strength and the dynamically generated gradient nano-structures, consisting of a nano-grained surface tribolayer and an ultra-fine grained subsurface layer, the B2 intermetallic binders promote an improved deformation compatibility with the WC skeleton, which contributes to the maintenance of robust contact surfaces. The current work thus highlights the important role of deformation compatibility on the durability of cemented carbides, which offers a new thread to future development of wear-resistant composite materials. Graphical abstract: Image 1